Constitutional Court Decisions in Progressive Law from Case Study on Outsourcing Worker Protection - Ahmad Ahmad; Rahmad Alan Kurniawan; Annelis Larasati Gufron; Fitri Anggraini; Salahudin Dirjon (Indonesian Journal of Law and Policy Studies, 2025)
This study explores how the Constitutional Court interprets the protection of outsourcing workers through a progressive legal perspective. It focuses on key aspects such as labor protection, progressive law, and judicial interpretation. The main aim is to understand the Court’s approach in safeguarding outsourcing workers and to uncover both normative and structural obstacles that affect its implementation. Using a qualitative normative method, this research relies on library-based analysis, examining Constitutional Court rulings, relevant legislation, and academic sources. The findings show that the Court tends to apply a progressive legal approach that prioritizes substantive justice and the protection of workers’ rights. However, challenges remain, including inconsistencies in regulations, limited oversight, and a lack of legal awareness among stakeholders. These issues highlight the need for stronger and more consistent progressive legal strategies moving forward.